2019
DOI: 10.1002/cam4.2203
|View full text |Cite
|
Sign up to set email alerts
|

RAD18 may function as a predictor of response to preoperative concurrent chemoradiotherapy in patients with locally advanced rectal cancer through caspase‐9‐caspase‐3‐dependent apoptotic pathway

Abstract: Neoadjuvant chemoradiotherapy (nCRT) has been widely applied to improve the local control rate and survival rate in patients with locally advanced rectal cancer (LARC), yet only part of LARC patients would benefit from nCRT. Therefore, it is imperative to predict the therapeutic outcome of nCRT. Here, we showed that RAD18, an E3 ubiquitin‐linked enzyme, played a fundamental role in predicting the response of LARC patients to nCRT. According to clinical data, patients with low RAD18 expression level in their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…The correlation between protein levels of specific genes and response to nCRT in rectal cancer has been extensively investigated by immunohistochemistry analysis of single candidate proteins and by explorative, proteomic approaches. The identified protein biomarkers are involved in diverse biological processes, such as DNA repair, 87 oncogenic signaling, 88 or apoptosis. 89 A selection of predictive, tissue-based protein markers is summarized in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between protein levels of specific genes and response to nCRT in rectal cancer has been extensively investigated by immunohistochemistry analysis of single candidate proteins and by explorative, proteomic approaches. The identified protein biomarkers are involved in diverse biological processes, such as DNA repair, 87 oncogenic signaling, 88 or apoptosis. 89 A selection of predictive, tissue-based protein markers is summarized in Table 2 .…”
Section: Introductionmentioning
confidence: 99%
“…RAD18 promotes the migration and invasion of esophageal squamous cell cancer via the JNK-MMPs pathway [ 9 ]. RAD18 high predicts the poor response to preoperative concurrent chemoradiotherapy in patients with locally advanced rectal cancer [ 10 ]. Nevertheless, the role of RAD18 in breast cancer has not been well explored.…”
Section: Introductionmentioning
confidence: 99%
“…RAD18, an E3 ubiquitin-linked enzyme, has a role in maintaining genome stability through multiple DNA repair pathways, including HR and PPR [22][23][24]. Several studies have shown that high expression of RAD18 confers resistance to chemotherapy or radiotherapy in multiple human cancers [25][26][27]. Thus, targeted inhibition of DNA repair proteins could affect drug response and improve therapy efficacy [28,29].…”
Section: Dysregulation Of Dna Repair Genes and Drug Responsementioning
confidence: 99%